Capacity precommitment and price transparency platforms. Theoretical benchmark and experimental evidence - Manfred Stadler; Werner Güth; Alexandra Zaby (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Price transparency in the sense of `more information for customers' is known to increase efficiency. However, the introduction of price transparency platforms does not only providemore information for customers but also for rival firms—who may (mis)use the legal information channel to collude. We experimentally investigate transparency platforms in the context of a capacity-then-price setting game. Price transparency is implemented by allowing firms to send non-binding price messages after capacity but before price choices. As such messages are cheap talk they do not affect the subgame perfect equilibrium of the game. In our experiment, however, we find collusive price choices when price messages are possible, especially when they are truthful. While we find strong support for the theoretically predicted negative relation between capacities and prices, participants frequently install excessive capacities, which, in turn, induce collusive pricing behavior.
Keywords: C72; C91; L41; 330